Faktor-Faktor Yang Berhubungan Dengan Perilaku Guru UKS Dalam Upaya Deteksi Dini Penderita Kusta Pada Anak Sekolah Dasar Di Kabupaten Blora - Pietojo, Harbandinah; Istiarti, Tinuk; Warijan, Warijan (Jurnal Promosi Kesehatan Indonesia, 2006)
Background : The prevalence of Leprosy in the world (1998) : Indonesia was placed in the big three after India and Brazil. In 2002, there were still 12 provinces and 111 regencies which the prevalence of Leprosy was over of 1/10.000 people. Fuethermore, data of Leprosy from 2000-2002 showed that Blora Regency was still placed in the big 10 among other Regencies in Central Java with prevalence >1/10.000 peole and proportionof Leprocy among the children was >1%. However, the proportion of Leprocy among children may be false as between the year 0f 2000-20002 there was no school survey done. Because of that, it was important to study the involment of Health School program teathers in the effort early detection of Leprosy clients. The study objective was to search factors that correlate with health school program (UKS) teachers’ behaviors in the effort of early detection of leprosy clients in elementary school students in Blora Regency.Method : This study was in eksplanatory research that employed survey sample method and cross sectionaltechnique. The study population was all Health School Program (UKS) Teachers’ in Blora Regency with the number of 712. the number of 88 samples was recruited from population using simple random smapling technique. The data were collected by interviewing using Quessionnares and analyzed by means of univariate,bivariat, and multivariate.Result : The result of this study showed there was a significant correlation between teachers’ salaraies and the practice of early detection of Leprosy clients with p value=0.04, between the rule of health workers and the practice of early detection of Leprosy client with p value 0.05. Together , variable salary with p value = 0.04 practice of early detection of Leprosy client (p value ≤ 0.05). Otherwise, the variable of the role og health workers with p value = 0.06 had no correlation with early detection of Leprosy clients (p value = 0.05). the most dominant factor that correlates with early diagnosis of Leprosy clients was salary of the sample with p value – 0.04.Keywords : early detection, leprosy, health school program teachers